Recreation as a Social Factor in Urban Development: A Response to Covid-19 Pandemic in Greater Jos, Nigeria (International Journal of Built Environment and Sustainability, 2022)
The importance of recreation cannot be overemphasised. Recreation refers to an activity that people engage in during their free time, and it is socially-inclined and has attendant values.  Inaccessibility to recreational areas affects the social wellbeing of residents, who will not have a sense of belonging when it comes to community development, hence a response to Covid-19.  Taking Greater Jos (Nigeria) as a case study, this paper assesses the social factors with regard to the provision of recreational facilities. The study also identified and mapped out recreational areas using the geographical positioning system. A questionnaire survey was conducted amongst the residents, age fifteen and above to authentically gauge their opinions on the study and, adopting stratified-random sampling considering the ten sectors according to the Greater Jos Master Plan. Results revealed that the residents had a good level of awareness of the presence of recreational facilities and high-quality recreational facilities, which were found mostly within the core of the city. The facilities fostered a high level of family and community bonding. However, the distance of recreational activity areas from their place of residence was what was rather disappointing for most people. Thus, the recent Covid-19 pandemic demand of social distancing negates social inclusion. The emphasis on social orientation and effective social inclusion of disadvantaged groups was conspicuously pronounced. Thus, appropriate and easy access to recreational facilities for all genders and ages must be provided closer to the people for effective services to promote their social lives and weaken the Covid-19 repulsive protocol.
Keywords: Social Impact, Recreational Facilities, Urban Development, Participation, and Covid-19